On the Selection of Effective Impulse Frequencies for the Specific Movements of Fish in an Electrical Field - Biswas, K. P. (Fishery Technology, 1971)
In order to determine effective pulse limits for Salmo irideus, Cyprinus carpio, Gasterosteus aculeatus, Tinca tinca, Salmo fario and ldus melanoius in impulse D. C. for galvanotaxis and galvanonarcosis, studies were carried out with rectangular and square impulses. The narcotizing pulse limits remained constant for each variety in an impulse D. C. of specific wave form. The anodic effect of fishes were better in square wave form and varied with the variation of temperature of surrounding medium. S. fario reacted better when placed parallel to the lines of electrical force. Transversal escape movement occurred when the axis of fish bodywas at right angles to the direction of current.